Self‐adaptive piezoelectric ceramic vibration system based on asymmetric piezoelectric cantilever for energy harvesting. Issue 5 (26th February 2018) - Fang, Mingwei; Liao, Qingwei; Wang, Jiawen; Qin, Lei; Zhong, Chao; Zhang, Di
Abstract: Micropower energy harvesting is one of key technologies for the micromation and practical development of wireless sensor and communication node networks. A self‐adaptive piezoelectric vibration system based on modified homogeneous strain asymmetric PZT piezoelectric ceramic cantilever beam for the micropower energy harvesting was designed and prepared. A vertical cantilever was designed at the first time to obtain the homogeneous state of stress which can largely increase the power output and energy harvesting efficiency of piezoelectric cantilevers. In order to achieve the self‐adaptive vibration, the asymmetric structure was adopted. Asymmetric cantilevers moved horizontally and changed the length of main cantilevers when affected by the variation in external frequency excitation, thus, the switching of resonant frequency was archived automatically without dissipating additional energy.